Advances in identifying archaeological traces of horn and other keratinous hard tissues. (November 2015) - O'Connor, Sonia; Solazzo, Caroline; Collins, Matthew
Abstract : Despite being widely utilized in the production of cultural objects, keratinous hard tissues, such as horn, baleen, and tortoiseshell, rarely survive in archaeological contexts unless factors combine to inhibit biodeterioration. Even when these materials do survive, working, use, and diagenetic changes combine to make identification difficult. This paper reviews the chemistry and deterioration of keratin and past approaches to the identification of keratinous archaeological remains. It describes the formation of horn, hoof, baleen, and tortoiseshell and demonstrates how identification can be achieved by combining visual observation under low-power magnification with an understanding of the structure and characteristic deterioration of these materials. It also demonstrates how peptide mass fingerprinting of the keratin can be used to identify keratinous tissues, often to species, even when recognizable structural information has not survived.